IMPLEMENTASI PROGRAM DIVERSIFIKASI PRODUK PANGAN LOKAL DI DINAS KETAHANAN PANGAN PROVINSI JAWA TENGAH - Riantika Aulia Putri; Ika Dyah Kumalasari; Bakti Utama (Universitas Wahid Hasyim, 2022)
In Indonesia, rice is a staple food that has high carbohydrates and is consumed by all Indonesian people. The high consumption of rice in Indonesia causes a decrease in the level of consumption of non-rice food and the low consumption of animal protein, vegetables, and fruits. Until the government made the slogan